2012
DOI: 10.1016/j.bbr.2011.10.048
|View full text |Cite
|
Sign up to set email alerts
|

Muscarinic receptor/G-protein coupling is reduced in the dorsomedial striatum of cognitively impaired aged rats

Abstract: Behavioral flexibility, the ability to modify responses due to changing task demands, is detrimentally affected by aging with a shift towards increased cognitive rigidity. The neurobiological basis of this cognitive deficit is not clear although striatal cholinergic neurotransmission has been implicated. To investigate the possible association between striatal acetylcholine signaling with age-related changes in behavioral flexibility, young, middle-aged, and aged F344 X Brown Norway F1 rats were assessed using… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
17
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 49 publications
2
17
0
Order By: Relevance
“…This age difference could not be accounted for by general discrimination learning deficits, as aged rats performed comparably to young on the initial discrimination rule. These results are in agreement with previously reported results using a multidimensional set-shifting paradigm in aged FBN rats (Nieves-Martinez et al, 2012) and are comparable with studies shown previously in aged rats of other strains, as well as aged monkeys and humans (Alexander et al, 2012; Barense et al, 2002; Beas et al, 2017, 2013; Berg, 1948; Moore et al, 2003). Together, these findings suggest that deficits in cognitive flexibility are a common feature of aging.…”
Section: 0 Discussionsupporting
confidence: 93%
“…This age difference could not be accounted for by general discrimination learning deficits, as aged rats performed comparably to young on the initial discrimination rule. These results are in agreement with previously reported results using a multidimensional set-shifting paradigm in aged FBN rats (Nieves-Martinez et al, 2012) and are comparable with studies shown previously in aged rats of other strains, as well as aged monkeys and humans (Alexander et al, 2012; Barense et al, 2002; Beas et al, 2017, 2013; Berg, 1948; Moore et al, 2003). Together, these findings suggest that deficits in cognitive flexibility are a common feature of aging.…”
Section: 0 Discussionsupporting
confidence: 93%
“…Studies in rodents, non-human primates, and humans show that performance on set shifting tasks is impaired in aged compared to young subjects (Barense et al, 2002; Bizon et al, 2012; Nieves-Martinez et al, 2012; Beas et al, 2013). Uniformly, such age-associated deficits are evident only when subjects are expected to adapt behavior following a rule shift but not during simple discrimination learning that does not require such flexibility (Robbins et al, 1998; Volkow et al, 1998; Barense et al, 2002; Moore et al, 2003, 2006; Ashendorf and McCaffrey, 2008; Nieves-Martinez et al, 2012; Beas et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Uniformly, such age-associated deficits are evident only when subjects are expected to adapt behavior following a rule shift but not during simple discrimination learning that does not require such flexibility (Robbins et al, 1998; Volkow et al, 1998; Barense et al, 2002; Moore et al, 2003, 2006; Ashendorf and McCaffrey, 2008; Nieves-Martinez et al, 2012; Beas et al, 2013). The present findings are consistent with this prior body of work, in that aged rats performed no differently than young on an initial (visual cue) discrimination, but were impaired in their acquisition of a subsequent left/right discrimination that required a shift in behavioral strategy.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, it can be suggested that the positive effect of enriched environment on water maze learning may also be related to the environmental impact on the survival of striatal cholinergic neurons. Along this line, it is noteworthy that aging-dependent alterations of cholinergic pharmacodynamics in the striatum were correlated with levels of water maze performance ) and that the M 2 /M 4 muscarinic receptor coupling in the striatum of cognitively impaired aged rats is reduced (Nieves-Martinez et al 2012).…”
Section: Spatial Cognition and Forebrain Cholinergic Neuronsmentioning
confidence: 92%